Asymptotics of the logarithmic derivative of an entire function of zero order - Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We find asymptotic formulas for the logarithmic derivative of a zero-order entire functionf whose zeros have an angular density with respect to the comparison function v(r) = r^λ(r), where λ(r) is the zero proximate order of the counting function n(r) of zeros of f.